Academy of Management Journal Editors' Forum - Rynes, Sara L.; Shapiro, Debra L. (Academy of Management Journal, 2005)
The article discusses the influence of academics on management practice in the U.S. One group of scholars believes that certain academic theories, particularly agency theory, have had a pronounced influence on management practice. Some contend agency theory has taught that managers cannot be trusted to do their jobs. Other scholars argue that management theorists have privileged certain stakeholders over others by conducting the vast majority of research from the perspective of top management or ownership.